2005
DOI: 10.1007/s10646-004-1352-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Organic Wastewater Contaminants on American Toad, Bufo americanus, Tadpoles

Abstract: Recent surveys of aquatic habitats suggest that organic wastewater contaminants (OWCs) may be common in aquatic ecosystems. However, relatively little is known about the impacts of OWCs on amphibians. We studied the lethal and sublethal effects of three OWCs (acetaminophen, caffeine, and triclosan) on American toad (Bufo americanus) tadpoles. High concentrations of triclosan increased activity, whereas acetaminophen had a significant effect on activity but there was no discernable pattern or trend with concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Smith and Burgett (2005) reported that environmentally relevant concentrations of caffeine (0.6-600 lg/l) did not affect the survivorship or activity of American toad (Bufo americanus) tadpoles. Similarly, Quinn et al (2008) classified caffeine as non-toxic based on acute (mortality) and chronic (feeding behavior, attachment, and growth) toxicity tests on the freshwater cnidarian Hydra attenuata.…”
Section: Introductionmentioning
confidence: 98%
“…Smith and Burgett (2005) reported that environmentally relevant concentrations of caffeine (0.6-600 lg/l) did not affect the survivorship or activity of American toad (Bufo americanus) tadpoles. Similarly, Quinn et al (2008) classified caffeine as non-toxic based on acute (mortality) and chronic (feeding behavior, attachment, and growth) toxicity tests on the freshwater cnidarian Hydra attenuata.…”
Section: Introductionmentioning
confidence: 98%
“…Studies assessing the potential environmental risk of pharmaceuticals in aquatic ecosystems have primarily focused on acute toxicity tests for higher organisms (e.g., invertebrates and fish; Smith and Burgett 2005;Crane et al 2006;Heckmann et al 2007) with limited data assessing effects on microbial organisms (Lawrence et al 2005). Microbial processes (respiration, nutrient uptake) are a holistic measure of ecosystem function as they are essential to nutrient flow and the transformation of organic matter (Hall and Meyer 1998;Hill et al 2000;Balser et al 2006;Nweke et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Next, they exposed X. laevis for 11 days to maximum acetaminophen concentrations of 1.0 mg/l and found no significant effect on mass or survivorship (Fraker and Smith, 2005). In separate experiments with Bufo americanus, Smith and Burgett (2005) noted increased mortality associated with 1 mg/l acetaminophen exposure. However, their study was considerably different than ours.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to using a different anuran model, Smith and Burgett (2005) exposed the organisms for much longer (14 days) and used post-hatch tadpoles which are more sensitive than pre-hatch tadpoles Kendall 2002, 2003). Despite these differences, Smith and Burgett (2005) did not see acetaminophen associated effects on body mass. Tadpoles in the present study did not have an increased mortality or growth reduction associated with 100 mg/l caffeine exposure.…”
Section: Discussionmentioning
confidence: 99%